Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Barabai Tahun 2021 - Khairunnissa Khairunnissa; Norfai Norfai; Zuhrupal Hadi (Universitas Baiturrahim, 2022)
Based on data from the Barabai Health Center, it was found that the incidence of hypertension in 2018 was 3,803 people, decreased in 2019 by 3,591 people but increased again in 2020 as many as 4,098 people. This study aims to determine the factors associated with the incidence of hypertension in the Barabai Health Center Work Area in 2021. The research method is an analytic survey with a cross sectional approach. A sample of 98 respondents used the Incidental Sampling technique. Statistical test using Chi Square Test. The results of the study on the incidence of mild hypertension were 40 respondents (40.8%), elderly age were 58 respondents (59.2%), female sex was 69 respondents (70.4%), had hypertension genetic factors as many as 73 respondents (74, 5%), do not have a smoking habit as many as 69 respondents (70.4%), have a habit of consuming salty food at risk as many as 66 respondents (67.3%). There is a relationship between age (p-value = 0.021), gender (p-value = 0.008), genetic factors (p-value = 0.002), smoking behavior (p-value = 0.008), habit of consuming salty food (p-value = 0.009) with the incidence of hypertension in the Barabai Health Center Work Area in 2021. It is recommended that the Public Health Center further improve promotive and preventive efforts to the community by providing easily accessible information facilities such as health education, socialization, distribution